Harmonic Suppressed Dipole Antenna with Size Reduction - Zulkurnain, Arief Ilmam; Hamzah, Shipun Anuar (Evolution in Electrical and Electronic Engineering, 2024)
Harmonic Suppressed Dipole Antenna with Size Reduction (HSDASR) offers a new method for designing a dipole antenna that incorporates size reduction and harmonic suppression. The rising need for small and effective antennas in contemporary communication systems demands creative ways to reduce physical dimensions and harmonic interference. Suppressing harmonic interference produced by non-linear components in the antenna system is the main goal. To reduce undesirable harmonics, the design makes use of stubs, harmonic trap structures, and other advanced methods. Achieving a small antenna size while preserving or improving performance metrics is a crucial objective. The use of methods of change the balun sizes from 100%, 75%, 50% and 25% is investigated in order to reduce size without sacrificing functionality. A thorough examination of previous studies on size reduction strategies, harmonic suppressed antennas and associated approaches is carried out. For modelling and simulating the proposed harmonic suppressed dipole antenna, simulation tools are used, such as CST Studio. The harmonic waves that were analyzed is at 0.9 GHz and 2.7 GHz. Operating signal is through 0 GHz until 3 GHz. Based on simulation results, the return loss, voltage standing wave ratio (VSWR), radiation pattern and gain was measured. The results show the function of adding stubs to the dipole antenna able to reduce around -20dB of harmonic. Based on the back to back balun, the return loss finds to be near to zero at 2.7 GHz and insertion loss finds to be less than -1dB. Using fabrication methods, the optimized design is turned into a prototype. The prototype is put through testing thus compare the results achieve with the simulation. The goal of the suggested size-reduction harmonic suppressed dipole antenna is to further the development of small and effective antenna designs. It is anticipated that the study will offer important new perspectives on how size reduction approaches and harmonic suppression strategies might be combined for real-world communication system applications.